Investigation of work zone crash casualty patterns using association rules - Weng, Jinxian; Zhu, Jia-Zheng; Yan, Xuedong; Liu, Zhiyuan (Accident analysis and prevention, 2016)
•An association rule method is proposed to analyze the characteristics and contributory factors of work zone crash casualties.•Association rules are centered on specific characteristics (e.g., drinking driving and not use of traffic control devices).•The association rule method can provide more understandable results in analysis of work zone crash casualty pattern. Investigation of the casualty crash characteristics and contributory factors is one of the high-priority issues in traffic safety analysis. In this paper, we propose a method based on association rules to analyze the characteristics and contributory factors of work zone crash casualties. A case study is conducted using the Michigan M-94/I-94/I-94BL/I-94BR work zone crash data from 2004 to 2008. The obtained association rules are divided into two parts including rules with high-lift, and rules with high-support for the further analysis. The results show that almost all the high-lift rules contain either environmental or occupant characteristics. The majority of association rules are centered on specific characteristics, such as drinking driving, the highway with more than 4 lanes, speed-limit over 40mph and not use of traffic control devices. It should be pointed out that some stronger associated rules were found in the high-support part. With the network visualization, the association rule method can provide more understandable results for investigating the patterns of work zone crash casualties.